2019
DOI: 10.1002/hep4.1319
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nonalcoholic Fatty Liver Disease Susceptibility Genes and Coronary Artery Disease

Abstract: Coronary artery disease (CAD) is the principal cause of death in patients with nonalcoholic fatty liver disease (NAFLD). The aim of the present study was to investigate whether NAFLD is causally involved in the pathogenesis of CAD. For this, previously reported NAFLD susceptibility genes were clustered and tested for an association with CAD in the Coronary Artery Disease Genome‐Wide Replication and Meta‐Analysis plus the Coronary Artery Disease Genetics (CARDIoGRAMplusC4D) Consortium data set. The role of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
(60 reference statements)
2
42
0
Order By: Relevance
“…3d), they also suggest that that plasma lipids have a greater impact on CAD risk than type 2 diabetes. Indeed, we recently expanded our genetic analyses to 12 NAFLD susceptibility genes (identified by either genome-wide association studies for NAFLD or NAFLD-related traits, or meta-analyses) and showed that the effects of these variants on CAD risk are largely accounted for by plasma lipids [55]. We observed a strong relationship between plasma lipids and CAD risk conferred by these NAFLD susceptibility genes [55].…”
Section: Covariatementioning
confidence: 86%
See 2 more Smart Citations
“…3d), they also suggest that that plasma lipids have a greater impact on CAD risk than type 2 diabetes. Indeed, we recently expanded our genetic analyses to 12 NAFLD susceptibility genes (identified by either genome-wide association studies for NAFLD or NAFLD-related traits, or meta-analyses) and showed that the effects of these variants on CAD risk are largely accounted for by plasma lipids [55]. We observed a strong relationship between plasma lipids and CAD risk conferred by these NAFLD susceptibility genes [55].…”
Section: Covariatementioning
confidence: 86%
“…Finally, variants in the membrane-bound O-acyltransferase domain-containing 7 gene (MBOAT7), which is involved in acyl-chain remodelling of phosphatidylinositols, have consistently been associated with NAFLD [53,54]. Of interest, the rs641738 T allele was not associated with CAD, nor with plasma lipids or type 2 diabetes [45,50,55].…”
Section: Covariatementioning
confidence: 99%
See 1 more Smart Citation
“…The clustering of 12 genetic variants associated with NAFLD by weighted fixed-effects statistical modeling showed no association with CAD or MI (OR: 1.00, 95% CI 0.99-1.01, p = 0.93) (Brouwers et al, 2019). Restricting this analysis to the four most validated genes (PNPLA3, TM6SF2, GCKR, and MBOAT7) also resulted in a null association (OR: 0.99, 95% CI 0.98-1.00) (Brouwers et al, 2019).…”
Section: Genetic Associations Not Discovered Through Genome Wide Assomentioning
confidence: 94%
“…Different endpoints have been used in NAFLD GWAS including histology, imaging-based hepatic fat content, serum liver enzymes, and presence of HCC, contributing to heterogeneity. Here we focus primarily on candidate NAFLD risk genes with consistent results in discovery GWAS or meta-analyses of GWAS, and validated using candidate gene studies, a strategy described in a recent study clustering NAFLD associated genes (Brouwers et al, 2019). We also highlight other genes not identified with GWAS, but have significant associations with CVD in retrospective studies or meta-analyses of retrospective studies, and outline their association with NAFLD ( Table 1).…”
Section: Genetics Of Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%